Pengembangan Media Pembelajaran Berbasis Proyek Pada Mata Pelajaran IPS Untuk Meningkatkan Kreativitas Siswa SD/MI - Rista Farida; Riska Latifatul Husna; Leha Arya Arvianti (Tim Jurnal STAI KH. Zainuddin Ponpes Mojosari, 2024)
This research aims to investigate the development of project-based learning media in enhancing students' creativity in Social Studies (IPS) subjects in elementary schools (SD/MI). This study is a qualitative descriptive research with library research subjects drawn from previous research journals. The study is based on several journals relevant to the topic of project based learning media development in Social Studies to enhance creativity in SD/MI. The findings indicate that project based media can increase student engagement in learning because it provides relevant and meaningful contexts for them. The use of project-based media often increases opportunities for students to explore topics in depth and engage in active learning.